(untitled) (Economics and region, 2024)
The article examines the current state of the global and regional footwear market and materials for its production. It is confirmed that using commodity science approaches to the analysis of the current state of the shoe market and materials for its manufacture, it is confirmed that a system of scientifically sound and practically significant conclusions can be created from statistical data on the shoe wardrobe of a modern consumer to describe the state, problems and prospects of the shoe market. The expediency of establishing the place and role of sustainable and environmentally friendly footwear on the modern world and regional market of the specified product is substantiated. The main factors that caused the increase in the volume of the global footwear market are presented. The current state of the footwear market by regional division and purpose of footwear (sports/household) is analyzed. The rapid growth rate of the production of sports shoes is substantiated. According to the results of the analysis of the global footwear market, it has been proven that at the current stage in the segment of ecologically clean footwear, household footwear is dominant. However, at the same time, the most growing segment of the market is environmentally friendly sports shoes. In particular, the global market of ecological shoes is experiencing a change in the stereotype, when environmental friendliness becomes a key factor in consumer decision-making about buying shoes. According to the results of recent studies, it has been confirmed that the dominant region in the world market of environmentally friendly shoes is the Asia-Pacific, and the region that develops the fastest is Europe. The leading role of sustainable and environmentally friendly footwear and materials for its production in shaping the modern range and quality of the specified product has been proven. A classification of the main factors that cause consumer supply and demand for sustainable and environmentally friendly footwear is proposed. Based on the analysis of the conducted sociological research, the main promising directions in shoe production are presented.